Ischemic heart disease deaths, disability-adjusted life years and risk factors in Fujian, China during 1990–2013: Data from the Global Burden of Disease Study 2013. (1st July 2016) - Xie, Xiao-Xu; Zhou, Wei-Min; Lin, Fang; Li, Xiao-Qing; Zhong, Wen-Ling; Lin, Shu-Guang; Li, Wen-Yan; Chen, Tie-hui; Ye, Ying; Hu, Xiang-Ju; Lin, Xi; Huang, Shao-Fen; et al.
Abstract: Objectives: Ischemic heart disease (IHD) is a large public health problem and is associated with a number of modifiable risk factors. The aim of this study was to estimate the IHD burden and attributable to risk factors in Fujian, China during 1990 to 2013. Methods: IHD deaths, disability-adjusted life years (DALYs) and attributable to risk factors were estimated as part of the Global Burden of Disease (GBD) 2013 Study. Statistical models were employed to produce comprehensive results of IHD deaths, DALYs and attributable to risk. Means and 95% uncertainty intervals (UIs) were calculated for mortality and DALYs. The median of the percent change and 95% UI were determined for the period between 1990 and 2013. Results: The age-standardized IHD deaths rate increased by 15.3% from 1990 [74.7 (95% UI 62.9–99.1) per 100, 000] to 2013 [82.7 (56.5–95.5) per 100, 000]. The age-standardized IHD DALYs has slightly decreased 8.8% from 1990 to 2013[from 1356.2 (1134.3–1732.1) to 1202.7 (879.6–1404.6) per 100, 000]. All risks combined account for 94.7% (92.9%- 96.0%) of IHD DALYs for all ages in 2013. The five leading risk factors for all ages IHD DALYs were high systolic blood pressure, high total cholesterol, smoking, diet high in sodium, and high fasting plasma glucose. Conclusion: Despite decreased age-standardized IHD deaths and DALY rate since 1990, population growth and aging led to a higher global burden of IHD in 2013. Behavioral, environmental, and metabolic risks can explain most of the IHD DALYs providing many opportunities for prevention. Highlights: Age-standardized DALYs from IHD have been declining in Fujian, China. The absolute numbers of IHD burden were largely increased. DALYs for IHD attributable to risk factors were estimated.